THE REFORM OF CORRUPTION ERADICATION IN INDONESIA: THE PRISMATIC LAW IN THE RECENT CONTEXT - Muhammad Fatahillah Akbar; Dian Agung Wicaksono (Fakultas Hukum Universitas Gadjah Mada, 2013)
This paper aims to investigate the reform of corruption eradication in Indonesia from three crucial aspects: the form of the Corruption Eradication Commission (KPK), the formulation of corruption in material and formal aspects, and other additional support system such as asset recovery and the protection of justice collaborator and whistle blower. This paper is a normative-legal research where it dissects secondary data which includes statutory regulations, various legal documents, researches, and other references relevant to corruption eradication in Indonesia. KPK could be strengthened in particular aspects with changes in regards its design of authority and its relationship with other authorities in corruption eradication process. Artikel ini bertujuan untuk meneliti reformasi pemberantasan korupsi dari tiga aspek penting: bentuk dari Komisi Pemberantasan Korupsi, perumusan korupsi dalam aspek materiil maupun aspek formiil, serta hal-hal pendukungnya seperti pemulihan aset dan perlindungan justice collaborator dan whistleblower. Tulisan ini merupakan penelitian hukum normatif yang menelaah data sekunder. Data sekunder yang ditelaah antara lain adalah peraturan perundang-undangan, berbagai dokumen hukum, penelitian, dan referensi lainnya yang relevan dengan pemberantasan korupsi di Indonesia. Komisi Pemberantasan Korupsi (KPK) akan diperkuat dalam aspek tertentu dengan diubahnya desain wewenang serta koordinasi hubungan antara KPK dan pihak berwenang lainnya dalam pemberantasan korupsi.